Field lab: equity research on Adidas AG - Heinold, Mario (2022)
Despite significant increases of Adidas’ share price throughout the past years, the following report concludes that the stock is still undervalued. Based on an extensive analysis of Adidas’ past performance and actions, the company’s position within the industry, as well as current industry trends, the report concludes that Adidas is well set for the future with revenues that are expected to increase with a CAGR of 7.0% until 2025. The main drivers are the expansion of middle-class population in Asian economies, a shift towards more sustainable sportswear products, and increasing sports participation globally.